Locked-in Syndrome: Insights into Etiology, Diagnosis, Management, and Quality of Life - Zelik, Urszula; Florczak, Wojciech; Śnieżna, Joanna; Dziewic, Jakub; Dzwonnik, Karol; Domino, Wiktoria; Trestka, Gabriela; Przygoda, Maria; Włodyka, Jagienka; Stępień, Kamila; et al. (Quality in Sport, 2025)
Locked-in Syndrome (LIS) is a rare and severe neurological condition resulting from damage to the ventral pons, leading to complete paralysis of voluntary muscles while preserving consciousness and cognitive function. This review consolidates current knowledge on the etiology, diagnosis, management, and quality of life in LIS, emphasizing its complexity and the need for a multidisciplinary approach.The condition’s etiological spectrum includes vascular events, trauma, infections, and demyelinating disorders, necessitating a comprehensive diagnostic approach integrating advanced neuroimaging and electrophysiological tools. Therapeutic strategies emphasize multidisciplinary care to address acute stabilization and long-term rehabilitation. Early interventions, such as thrombolysis and respiratory support, combined with advanced neurorehabilitation techniques, have shown promise in improving outcomes. Notably, patients with LIS often report a higher-than-expected quality of life, attributed to strong social support, emotional resilience, and access to assistive technologies, highlighting the resilience of patients in adapting to extreme physical limitations. This review underscores the importance of individualized care that aligns with patient values and emphasizes the necessity of further research. Future studies should focus on refining diagnostic methods, advancing communication technologies, and exploring the psychological dynamics affecting both patients and caregivers. By fostering a collaborative, patient-centered approach, the quality of life and care for individuals with LIS can be significantly improved.